Spontaneous thoracolumbar hematomyelia secondary to hemophilia B in a cat. Issue 2 (25th July 2015) - Barnard, Laura R; Leblond, Guillaume; Nykamp, Stephanie G; Gaitero, Luis
Case summary: A 10-year-old neutered male domestic shorthair cat presented for evaluation of acute onset of paraplegia with loss of nociception and thoracolumbar spine hyperesthesia and no history of trauma. Activated partial thromboplastin time (aPTT) was markedly prolonged, and specific coagulation factor testing revealed a factor IX level of 4% of normal activity, confirming the presence of mild hemophilia B. Prior abnormal bleeding had occurred at the time of castration as a kitten, as well as with laceration to a toe. Advanced imaging, including computed tomography (CT) and magnetic resonance imaging (MRI) of the thoracolumbar spine, confirmed the presence of multifocal intradural and intramedullary spinal cord hemorrhage through demonstration of focal ring enhancement on CT and multifocal areas of signal void on gradient echo T2* images on MRI. Despite factor IX supplementation through the use of fresh frozen plasma transfusions and normalization of the aPTT time, the cat's neurological status did not improve. Owing to repeated urinary tract infections, with increasing resistance to antibiotic therapy, the cat was ultimately euthanized. Post-mortem examination showed no evidence of another underlying primary pathology for the hematomyelia. Relevance and novel information: To our knowledge, this case demonstrates the first reported occurrence of spontaneous hematomyelia secondary to hemophilia B in a cat.